Predicting water stress tolerance of malting barley varieties with seedlings PEG-reactions - Skribanek, Anna; Tomcsányi, András (Acta Biologica Szegediensis, 2008)
We analyzed the correlation between 32 malting barley variety seedlings PEG-reactions and the water stress tolerance. We characterized the water stress tolerance with the yield differences of the year 2007 (extreme arid) and 2006 (normal fall). Under PEG solution effect the proline and sucrose content was higher, and the roots and leaves growth was lower. The correlation between them was r=0.32-0,49. After the contraction of the four best correlated PEG-reactions attribute with water stress the correlation of the contracted PEG-reaction index improved up to r=0,65.